Diabetes and Addictive Disorders - Balhara, Yatan Pal Singh; Bajaj, Sarita; Tiwaskar, Mangesh; Joshi, Ameya; Deshmukh, Vaishali (Journal of Social Health and Diabetes, 2019)
Prevalence of addictive disorders among persons with diabetes mellitus (DM) (type 1 and type 2) ranges from 9.6 to 29%. Excessive and problematic use of psychoactive substances in persons with diabetes results in poor glycemic control with frequent hyperglycemic crisis. Tobacco, alcohol, cannabis, benzodiazepines, inhalants, and stimulants are common psychoactive substances used among persons with diabetes in India. The daily use of alcohol by men and women with DM should not exceed 15 and 30 g of ethanol, respectively. Use of other psychoactive substances is not recommended for persons with DM. Various screening tools exist for assessing substance abuse like WHO-ASSIST, Alcohol Use Disorders Identification Test (AUDIT), Fagerström Test for Nicotine Dependence (FTND), and Opioid Risk Tool. Integrated management of co-occurring addictive disorder and DM is recommended. Psychosocial treatments for substances include brief interventions (BIs), motivational interviewing, contingency management, relapse prevention, and cognitive behavior therapy
Keywords: psychoactive substance abuse; screening tools; behavior therapy